Magnesium technology 2014 : proceedings of a symposium sponsored by the Magnesium Committee of the Light Metals Division of the Minerals, Metals & Materials Society (TMS) held during TMS2014, 143rd Annual Meeting & Exhibition, February 16-20, 2014, San Diego Convention Center, San Diego, California, USA - Alderman, Martyn; Manuel, Michele V.; Hort, Norbert; Neelameggham, Neal R. (Springer, 2016)
The Magnesium Technology Symposium, the event on which this collection is based, is one of the largest yearly gatherings of magnesium specialists in the world. Papers in this collection represent all aspects of the field, ranging from primary production to applications to recycling. Moreover, papers explore everything from basic research findings to industrialization. This volume covers a broad spectrum of current topics, including alloys and their properties; cast products and processing; wrought products and processing; forming, joining, and machining; corrosion and surface finishing; ecology; and structural applications. In addition, there is coverage of new and emerging applications in such areas as hydrogen storage.
International conference proceedings.
Includes indexes.
Keywords: Magnesium -- Metallurgy -- Congresses.; Magnesium alloys -- Congresses.; Magnesium founding -- Congresses.; elektronické knihy; electronic books